Desain Modul Ajar Energi Alternatif Berbasis Project-Based Learning Dengan Alat Peraga Turbin Air Pelton - Husaini, Ibrahim; Fachri, Muhammad Rizal (Jurnal Pendidikan Teknik Elektro, 2025)
This study aims to design a teaching module based on Project-Based Learning (PjBL) in the topic of alternative energy, with a focus on utilizing a Pelton water turbine teaching aid as a learning medium. The background of this research lies in the importance of mastering renewable energy concepts and practical skills for students in addressing energy crises and promoting environmental sustainability. The module is designed to encourage active, collaborative, and project-based learning that integrates theoretical knowledge with hands-on practice through experiments using the Pelton turbine teaching aid. The development process of the module includes needs analysis, content design, feasibility testing, and performance evaluation in a laboratory context. The results show that the module enhances students’ understanding of renewable energy concepts, technical skills, and positive scientific attitudes. This module is expected to serve as an applicable learning innovation that supports students’ competencies in the field of Electrical Engineering Education.